Prospective Technological Study of Plant Species through Patent Documents - Wanise Borges Gouvea BARROSO (Revista CENIC. Ciencias Biológicas, 2010)
The research data has a purpose to show the Technology Prospection for four types of plants, randomly chosen from the National List of Medicinal Plants of Interest to SUS (Brazilian Unified Health System) - RENISUS; these are Arrabidaea chica, Artemisia absinthium, Bidens pilosa and Curcuma longa. The Derwent Database, available in the Capes Periodical Portal, Google, Brazilian PTO and Espacenet were the websites used to make this research. The main objective was to determine if innovations that contain these plants have been protected by the patents, also identify who were the principal assignees, the evolution profile of the patent applications, in which areas they were being filed in and in which period they were filed. It was found that the species that presents a larger amount of deposits is Curcuma longa with 307 patent applications, followed by Bidens pilosa with 78 patent applications. The species with fewer patent applications are Artemisia absinthium and Arrabidaea chica with 25 patent applications and 3, respectively: Although the species studied are part of the RENISUS table, the study identified only one deposit of a patent application in Brazil, which shows a trend of development of future research for using of the species to obtain new herbal medicines.